Amendments to accounting policies in accordance with IASB requirements ("Journal "U". Economy. Management. Finance.", 2022)
The article discusses the need to amend the accounting policy for the purposes of IFRS. Accounting policy under IFRS and its formation are based on the principles stipulated by international standards.
Keywords: accounting policy; IFRS; revision of accounting policy